A multi-tier based clustering framework for scalable and energy efficient WSN-assisted IoT network - Shukla, Anurag; Tripathi, Sarsij (Wireless networks, 2020)
The effectiveness of wireless sensor network (WSN) in Internet of Thing (IoT) based large scale application depends on the deployment method along with the routing protocol. The sensor nodes are an important component of WSN-assisted IoT network running on limited and non-rechargeable energy resource. The performance of WSN-assisted IoT is decreased, when network is deployed at large area. So, developing robust and energy-efficient routing protocol is a challenging task to prolong the network lifetime. In contrast to the state-of-the-art techniques this paper introduces Scalable and energy efficient routing protocol (SEEP). SEEP leverages the multi-hop hierarchical routing scheme to minimize the energy consumption. To achieve scalable and energy efficient network, SEEP employs a multi-tier based clustering framework. The network area in SEEP is divided into various zones with the help of proposed subarea division algorithm. The number of zones in the network are increased as the network size increases to avoid long-distance communication. Every zone is divided into certain number of clusters (sub-zones) and the number of clusters are increased towards the base station, whereas the zone width is decreased. In every cluster, some of the optimal nodes are promoted as a Relay Node (RN) and Cluster Head (CH). Normal nodes send their sensed data to the base station via local RN and CH in a multi-hop way. Furthermore, propose protocol provides a trade-off between distance and energy to prolong the network lifetime. In the proposed framework, static and mobile scenarios have been considered by applying Random walk and Random waypoint model for node mobility in simulation to make it more realistic as the various application of WSN-assisted IoT. The effectiveness of SEEP is examined against LEACH, M-LEACH, EA-CRP, TDEEC, DEEC, SEP, and MIEEPB, and result indicates that SEEP performs better for different network metrics: network lifetime, scalability, and energy efficiency.